The management of culture and environment of madrasah: Its implementation and challenges in industrial revolution era 4.0 - Herson Anwar; Lukman Arsyad; Arten H Mobonggi (Jurnal Prima Edukasia, 2020)
This study aims to review the implementation of the management of culture and environment of madrasah and the challenges faced, especially the private Madrasah at Gorontalo. The method used in this study is a naturalistic-qualitative study. The data were collected through observation, interview, and documentation. The findings obtained showed that the culture and environment at the private Madrasah Ibtidaiyah at Gorontalo were various in physical culture and behavioural culture. The physical culture can be seen from the physical appearance of madrasah which has different characteristics. The form of physical culture involved can be seen from the facilities, school building with fence, motto, and writing in the wall which support the development of expected culture. The behavioural culture can be seen from religious culture, discipline culture, and the implementation of the rules, achievement and competition culture, reading and clean culture. The implementation of the management of culture and environment of madrasah is in line with the vision, mission, and the goals of the school realized in the form of programs regarding the creation of culture and environment of madrasah by improving the participation of all people in madrasah in order to optimize the facilities which support cultural values that become the priority of each private Madrasah Ibtidaiyah in Gorontalo. In order to solve the problems, the awareness and commitment of people in madrasah are totally required especially in the fixing of the learning system and the enforcement of disciplines, which cultural values are important and unimportant. Besides that, the harmonious cooperation among all people in madrasah is essentially needed in managing the culture and environment of madrasah to elevate the competitiveness.